Transforming Multi-Platform Digital Zakat Fundraising Among Millennials And General Z - Mariyatul Qibthiyyah Mery; Muhammad farid; indra hidayatullah; Nurhafid Ishari (LP2M IAIN Palopo, 2026)
This study aims to analyze the transformation of multi-platform digital fundraising of zakat funds among Millennials and Generation Z in the context of changing Islamic philanthropic behavior in the digital era. This phenomenon is significant because advances in financial technology and social media have transformed how young Muslim generations interact with religious practices, particularly in fulfilling zakat obligations. This research employs a qualitative approach using a case study method, enabling the researcher to explore users’ meanings and experiences in utilizing various digital zakat platforms. Data were collected through semi-structured interviews, participatory observation, and digital documentation involving informants from zakat management institutions, platform developers, as well as young donors from the Millennial and Generation Z groups who actively use digital zakat applications.The findings reveal three main themes: (1) increased digital trust in zakat institutions due to transparency and transaction security; (2) the emergence of technology-based religious motivation that positions digital zakat as an expression of modern spirituality; and (3) the role of social media in shaping philanthropic awareness through narratives of empathy and online solidarity. These findings indicate that zakat digitalization not only transforms fundraising mechanisms but also reconstructs how young generations interpret worship and social participation.This study contributes theoretically to the development of the concepts of digital religiosity and the Technology Acceptance Model (TAM) within the context of Islamic philanthropy. Practically, the findings provide guidance for zakat institutions in optimizing transparent and participatory digital communication strategies. Future research is recommended to examine the influence of social media algorithms on digital religious behavior to broaden understanding of zakat dynamics in the era of technological transformation